Potensi Antijamur Ekstrak Andaliman (Zanthoxylum acanthopodium) terhadap Candida albicans - Fri Rahmawati; John Jackson Yang; Irene Rumiris Bavelina (Jurnal Pro-Life, 2022)
Andaliman (Zanthoxylum acanthopodium DC) is a plant that grows and is widely used in Sumatra, especially by the Batak tribe (North Sumatra). Andaliman is empirically used for the treatment of diarrhea, toothache, and is a natural food preservative. Resistance increase of antifungal drugs to Candida albicans, so research is needed to find new ingredients that are effective as antifungals. The use of traditional medicines derived from plants can be an alternative for the community as an antifungal. The aim of the research was to determine the class of active compounds and the potential of andaliman fruit extract to inhibit the growth of C. albicans. The extraction process uses the maceration method with 70% ethanol and aquadest as a solvent. The antifungal activity test method used was the disc diffusion method and the phytochemical test using the Harborne method. The concentration of andaliman extract used was 50%, 40%, 30%, 20% and 10%, positive control was fluconazole and negative control was distilled water. The results showed that the andaliman extract was able to inhibit the growth of C. albicans with the lowest concentration of 10%. Andaliman extract (ethanol and aquadest) contains active compounds in the form of flavonoids, tannins, saponins, and steroids.